Microbial volatile organic compounds in moldy interiors: A long‐term climate chamber study. (23rd August 2012) - Schuchardt, Sven; Strube, Andrea
Abstract The present study simulated large‐scale indoor mold damage in order to test the efficiency of air sampling for the detection of microbial volatile organic compounds (MVOCs). To do this, a wallpaper damaged by condensation was stored in a climate chamber (representing a hypothetical test room of 40 m3 volume) and was inoculated with 14 typical indoor fungal strains. The chamber ventilation conditions were adjusted to common values found in moldy homes, and the mold growth was allowed to continue to higher than average values. The MVOC content of the chamber air was analyzed daily for a period of 105 days using coupled gas chromatography/mass spectrometry (GC–MS). This procedure guarantees MVOC profiling without external factors such as outdoor air, building materials, furniture, and occupants. However, only nine MVOCs could be detected during the sampling period, which indicates that the very low concentrated MVOCs are hardly accessible, even under these favorable conditions. Furthermore, most of the MVOCs that were detected cannot be considered as reliable indicators of mold growth in indoor environments.